Exploring the Complexity of the Interaction between T. rubrum and S. aureus/S. epidermidis in the Formation of Polymicrobial Biofilms - Belizario, Jenyffie A. [UNESP]; Bila, Níura M. [UNESP]; Vaso, Carolina O. [UNESP]; Costa-Orlandi, Caroline B. [UNESP]; Mendonça, Matheus B. [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Pires, Regina H.; Mendes-Giannini, Maria José S. [UNESP] (MDPI, 2024)
Dermatophytes associated with bacteria can lead to severe, difficult-to-treat infections and contribute to chronic infections. Trichophyton rubrum, Staphylococcus aureus, and Staphylococcus epidermidis can form biofilms influenced by nutrient availability. This study investigated biofilm formation by these species by utilizing diverse culture media and different time points. These biofilms were studied through scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM), biomass, metabolic activity, and colony-forming units (CFUs). The results revealed that mixed biofilms exhibited high biomass and metabolic activity when cultivated in the brain heart infusion (BHI) medium. Both bacterial species formed mature biofilms with T. rubrum within 72 h, irrespective of media. The timing of bacterial inoculation was pivotal in influencing biomass and metabolic activity. T. rubrum’s development within mixed biofilms depended on bacterial addition timing, while pre-adhesion influenced fungal growth. Bacterial communities prevailed initially, while fungi dominated later in the mixed biofilms. CLSM revealed 363 μm thick T. rubrum biofilms with septate, well-developed hyphae; S. aureus (177 μm) and S. epidermidis (178 μm) biofilms showed primarily cocci. Mixed biofilms matched T. rubrum’s thickness when associated with S. epidermidis (369 μm), with few hyphae initially. Understanding T. rubrum and Staphylococcal interactions in biofilms advances antimicrobial resistance and disease progression knowledge.
Keywords: biofilms; dermatophytes; dual-species biofilms; Staphylococcus aureus; Staphylococcus epidermidis; Trichophyton rubrum